PENGEMBANGAN MEDIA ALAT BANTU KAYANG PEMBELAJARAN SENAM LANTAI - Ary Budhi Prasetya; Ranu Baskora A.P (Universitas Negeri Semarang, 2016)
The purpose of this study was to produce a model of media development tools for learning gymnastics floor Kayang in class VIII SMP Negeri 1 Rembang Kragan.The method used is the development of Borg & Gall. From the test results obtained from the evaluation of experts, namely, physical education specialists 82.5% (meets both criteria), 92.5% learning experts (meet criteria very well). Small-scale trial results 96% (meets the criteria very well), and a large-scale trial of 97.5% (meet criteria very well). Based on the research results, it can be concluded that this Kayang media tools can be used for learning Penjasorkes in gymnastics floor for class VIII SMP Negeri 1 Rembang Kragan.